260. Effect of Antibiotic Indications on Clinician Documentation and Pharmacy Workflow in Hospitalized Children. (26th November 2018) - Scardina, Tonya; Kociolek, Larry; Patel, Sameer
Abstract: Background: Documentation of antibiotic indication at the time of order entry is mandated by the Centers for Disease Control and Prevention. We evaluated the effect of this mandate on the accuracy of clinician documentation and pharmacy work flow in hospitalized children. Methods: Documentation of indication at our institution was required beginning March 30, 2017. All patients ≤18 years old that received ≥1 dose of intravenous (IV) vancomycin (VAN) or IV/intramuscular ceftriaxone (CTX) during a 1 month preintervention period and three postintervention study periods (at 0, 3, and 6 months following implementation) were included. Patients were only included once per study period. Data included timing of antibiotic administration, indication for use, infection at body site requiring potential dose modification, dose modification, and agreement between order and progress note. Results: Median age of patients was 4.2 years. Most common indications for VAN (total: 789) were sepsis syndrome (26%, N = 204), febrile neutropenia (12%, N = 95), and suspected catheter-related bloodstream infection (10%, N = 77) and for CTX (total: 1, 071) were sepsis syndrome (12%, N = 127), perforated appendicitis (12%, N = 125), and urinary tract infection (10%, N = 107). Conclusion: Agreement between orders and progress notes was less than 50% during the postintervention period for both antibiotics. Median time to administration decreased for CTX, but not VAN. Antibiotic modifications were more common in the postintervention periods. Disclosures: L. Kociolek, Alere/Techlab: Investigator, Research support S. Patel, Merck: Grant Investigator, Grant recipient and Research grant